Optimalisasi Pencatatan Transaksi dan Pengelolaan Piutang untuk Memperkuat Kinerja Keuangan - Muharni Muharni (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the accuracy of transaction recording and accounts receivable management in improving the financial performance of Umi Salamah Clothing Shop, a small business that still applies a manual bookkeeping system. The research employed a descriptive qualitative approach through direct observation and interviews with the owner and administrative staff, supported by the review of transaction and receivable documents for a six-month period. The findings indicate that most transactions were recorded correctly, although several errors were identified, leading to less reliable financial information. The management of receivables was fairly effective, yet delays in customer payments affected cash flow stability. These results highlight the essential role of accurate recording and structured credit control in enhancing business profitability and financial resilience. The study concludes that improvements in bookkeeping practices and the implementation of clearer receivable policies are required to strengthen financial performance and support the sustainability of the business.